2019
DOI: 10.1002/jor.24254
|View full text |Cite
|
Sign up to set email alerts
|

Abaloparatide, a PTH receptor agonist with homology to PTHrP, enhances callus bridging and biomechanical properties in rats with femoral fracture

Abstract: Fractures typically heal via endochondral and intramembranous bone formation, which together form a callus that achieves union and biomechanical recovery. PTHrP, a PTH receptor agonist, plays an important physiological role in fracture healing as an endogenous stimulator of endochondral and intramembranous bone formation. Abaloparatide, a novel systemically‐administered osteoanabolic PTH receptor agonist that reduces fracture risk in women with postmenopausal osteoporosis, has 76% homology to PTHrP, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…Further studies with increased clarity on the osteoblastic and osteoclastic responses of both agents relative to fracture healing may be valuable to discern potential clinical applications. The most recent study of abaloparatide and fracture healing was a rat study that compared two doses (5 and 20 μg/kg/d) in 12‐week‐old rats for 4 or 6 weeks . Abaloparatide treatment resulted in greater callus area and volume, higher bridging scores, and greater callus maximum load and stiffness versus vehicle controls.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further studies with increased clarity on the osteoblastic and osteoclastic responses of both agents relative to fracture healing may be valuable to discern potential clinical applications. The most recent study of abaloparatide and fracture healing was a rat study that compared two doses (5 and 20 μg/kg/d) in 12‐week‐old rats for 4 or 6 weeks . Abaloparatide treatment resulted in greater callus area and volume, higher bridging scores, and greater callus maximum load and stiffness versus vehicle controls.…”
Section: Resultsmentioning
confidence: 99%
“…The most recent study of abaloparatide and fracture healing was a rat study that compared two doses (5 and 20 μg/kg/d) in 12-week-old rats for 4 or 6 weeks. (85) Abaloparatide treatment resulted in greater callus area and volume, higher bridging scores, and greater callus maximum load and stiffness versus vehicle controls.…”
Section: Pth Effects On Healing Of Atypical Femoral Fracturesmentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast to treatment with PTH, no studies have previously investigated the effect of ABL in relation to disuse-induced bone loss in rats. However, ABL has previously been studied in intact ( 42 , 43 ), ovariectomized ( 44 , 45 ), and orchiectomized animals ( 46 , 47 ), as well as during fracture healing in mice ( 26 ) and rats ( 48 ). These studies have demonstrated bone anabolic properties of ABL in accordance with those established in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32] Abaloparatide also improved the early bridging and biomechanical stability of long bone fractures in rats, with bridging showing significant relationships with the extent of callus chondrogenesis and osteogenesis. 33 Spinal fusion is associated with chondrogenesis and osteogenesis, 2,3,6 and chondrogenic responses have been demonstrated with high-dose teriparatide therapy in spinal fusion models 3,4 and with abaloparatide in mesenchymal cell cultures. 34 The current study is the first to examine the effects of abaloparatide as a postoperative adjuvant therapy in animals undergoing noninstrumented PLF.…”
Section: Introductionmentioning
confidence: 99%